Making health information personal: how anecdotes bring concepts to life - Ricketts, Mitchell S. (Information Science Reference, 2013)
Research suggests people often fail to understand the personal relevance of generalized health information. To make health information more meaningful, communicators can employ anecdotes that take the form of instructive stories about the illnesses or injuries of particular people. Appropriate anecdotes may help audiences internalize health information by triggering insights such as: “I see how that could happen to me…I’d better take action.” Vivid anecdotes appear to activate many of the same neurological pathways that help us extract meaning from direct experience and observation. By eliciting vivid imagery, provoking deep thought, and forging lasting memories, anecdotes may shape beliefs and behaviors to nearly the same extent as a lived event. This chapter explores methods for integrating anecdotes into health messages to increase personal relevance and prompt important changes in health-related behavior.
Keywords: Health information; Anecdotes; Health messages